The development of a career guidance module to improve the understanding of career planning among students at MAN Sorong - Almuhaimin Sarnav Ituga (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to: (i) assess the understanding of career planning among the 10th-grade students at MAN Sorong; (ii) create a practical, valid, and engaging career guidance module aimed at improving their comprehension of career planning; and (iii) demonstrate that the utilization of this module can enhance the understanding of career planning among these students. Adopting the research and development framework established by Borg and Gall, this study employed scales, observations, and Focus Group Discussion (FGD) for data collection. The results showed that: (i) the level of career planning understanding among 10th-grade students at MAN Sorong was low, emphasizing the necessity for a career guidance module as a counseling tool to enhance their understanding; (ii) the developed career guidance module was deemed valid, practical, and engaging, as affirmed by the utility, feasibility, and accuracy assessments conducted by experts and field practitioners; and (iii) implementing the career guidance module effectively enhances the understanding of career planning among 10th-grade students at MAN Sorong. Additionally, the module’s acceptability is confirmed through a limited group test involving 10 students who are ready to utilize it in school to improve their grasp of career planning.